CONTRIBUIÇÃO DA TEORIA PSICANALÍTICA ̶ DE FREUD, LIDA COM LACAN – À ESCUTA DE CRIANÇAS NO CONTEXTO DA JUSTIÇA DA INFÂNCIA E JUVENTUDE. - SANTOS, Ana Meire Filgueira dos (2018)
The present study focuses on the contributions of psychoanalytic theory to listen to children in the context of Justice for children and youth, which aims to identify a subjective place children in judicial situation, certifying the authenticity of their narratives, with the foundations of the theory of the subject proposed by theoretical psychoanalysis of Freud, Lacan handles. It is a theoretical research qualitative in nature, based on the psychoanalytic method, which is not intended for obtaining accurate data for proof of hypothesis, but undertake the analysis of an experiment in which the researcher is involved and is affected by it. Deals with the integration of psychology and legal means some of the remarkable moments along that route, among which stands out the presence of the psychologist at Justice for children and youth, legally established as can be seen in the Statute of the child and adolescent (Law 8,069/1990), with the purpose of realization of psychological expertise with children and adolescents. Strengthening the child role, comes more recently with the Legal framework of the early childhood (13,257 Law/2016), which supports the effective participation of the child in every action to be undertaken by public institutions and should be heard as its forms expression peculiar The evidence presented by Freud (1856-1939) in psychoanalytic theory in your convinced of the legitimacy of that Psychic apparatus cannot be reduced to consciousness, but is determined the unconscious, and suffers significant and frequent determinations. Lacan (1964/1985) ratifies the subject of the unconscious and your constitution and articulation by the language, from the relation with the other. In this sense, adopting this perspective, psychologist active in justice for children and youth is dedicated to listening your subject that appears between the lines of the narratives of the child and believes that the psychic is intertwined with the conscious. Therefore, the focus of your listen not secure fenomênicos data, i.e. stop just looking for information proving the fact reported, but to go beyond, a singularity from the subject.